In Vitro models of leukemia development: the role of very small leukemic stem-like cells in the cellular transformation cascade - Lica, Jan Jakub; Jakóbkiewicz-Banecka, Joanna; Hellmann, Andrzej (Frontiers in Cell and Developmental Biology, 2025)
Recent experimental findings indicate that cancer stem cells originate from transformed very small embryonic-like stem cells. This finding represents an essential advancement in uncovering the processes that drive the onset and progression of cancer. In continuously growing cell lines, for the first time, our team’s follow-up research on leukemia, lung cancer, and healthy embryonic kidney cells revealed stages that resembles very small precursor stem cells. This review explores the origin of leukemic stem-like cells from very small leukemic stem-like cells establish from transformed very small embryonic-like stem cells. We explore theoretical model of acute myeloid leukemia initiation and progresses through various stages, as well basing the HL60 cell line, present its hierarchical stage development in vitro, highlighting the role of these very small precursor primitive stages. We also discuss the potential implications of further research into these unique cellular stages for advancing leukemia and cancer treatment and prevention.